IMPLEMENTATION OF PROBLEM SOLVING LEARNING TO INCREASE STUDENT LEARNING OUTCOMES ON CHEMICAL BONDING MATERIALS IN CLASS X IPA 1 SMA NEGERI 1 PURI - Solikhatiningsih (Jurnal Scientia, 2022)
This study aims to determine the improvement of learning quality, activeness and student learning outcomes in the application of problem solving learning in class X IPA 1 SMA Negeri 1 Puri. This research is classroom action research (CAR) which consists of two cycles with each cycle consisting of planning, implementation, observation, and reflection stages. This research was conducted in class X IPA 1 SMA Negeri 1 Puri in the odd semester of the 2019/2020 school year involving 30 students. The results showed that problem solving learning made it easier for teachers to carry out learning so that learning became quality, which was marked by an increase in the assessment of the implementation of learning, from 2.6 (good) to 3.8 (very good) in the second cycle and student activities also showed students were very active, as evidenced by the increase in student activity from 86.67% in the first cycle to 93.33% in the second cycle. In addition, problem solving learning makes it easy for students to master competencies. This is evidenced by an increase in student learning outcomes, namely an increase in mastery learning outcomes from 72.22% in the first cycle to 88.89% (completed).